Farmers’ Perception and Adoption of Abiotic Stress Tolerant Rice Varieties in Rain-fed Lowlands of North Eastern Uttar Pradesh - Ravindra,; Singh, Alka (Indian Journal of Extension Education, 2019)
The farmers’ practice of growing old but long tested improved and traditional rice varieties due to their experience and perception about varietal traits suitability to the local environment seem to be major determinants of technology choices in the region. The Varietal diversity index (VDI) was employed to know rice varietal diversity at farm level in the region. Likert scale was used to measure preferences and perceptions of rice varietal traits and constraints of improved and traditional rice varieties of the study area. Maximum number of sample farmers reported to have purchased seed every alternate year, while another one fifth of farmers purchased rice seed after every two years. Among the varietal attributes which farmers from the region demand in new rice variety, higher yield and tolerance to drought and submergence together scored the highest in terms of preference scale in both the districts of the region due to frequent occurrences of drought and flash floods.
Keywords: Abiotic Stress; Adoption; Farmer; Lowland; Perception; Rice Varieties; Tolerant